Augmenting farmers’ income through participatory seed production of toria in NEH region - Verma, Harendra; Seyie, Azeze; Kalita, H. (Indian Farming, 2024)
Toria is one of the most important oilseed crop that has been cultivated immediately after the harvest of kharif rice in rainfed areas to enable efficient utilization of residual soil moisture for enhancing the cropping intensity of the Nagaland state. The productivity of the crop is lower in the farmer's field due to non-adoption of improved varieties, timely unavailability of quality seed, water scarcity in rabi. Training on participatory seed production of toria was imparted and a field day was organized involving 30 farmers’ of different villages of Dimapur district during the rabi season of 2021-22. Farmers were encouraged to adopt and cultivate TS-67 toria variety due to its high yield and short duration, making it an ideal rabi season crop immediately after harvesting lowland rice and continue the participatory seed production. The proper dissemination of scientific cultivation practices along with seed production techniques has increased the yield by 53.22% (9.5 q/ha) leading to a benefit cost ratio of 2.5:1 over farmers' practice (1.8:1). This adoption has increased cropping intensity, boosted oilseed production and improved farmers’ income and livelihoods.